Classical Pentecostals" literalist reading of the Bible: Challenges and solutions - Nel, Marius (HTS teologiese studies, 2024)
The study’s setting is South African classical Pentecostals’ use of hermeneutics that became aligned with conservative Evangelicals’ fundamentalist practices since the 1940s. It addresses the lack within Pentecostal scholarship to relate some Pentecostal excesses and related abuses, such as the prosperity message, to the movements’ common literalist-biblicist hermeneutics Bible reading practices. It argues that an alternative hermeneutic to their hermeneutics true to the movement’s original ethos can protect them from such excesses. The study utilises a comparative literature analysis without any empirical research methods. The article developed a scholarly founded Pentecostal hermeneutical model by emphasising three propria: that the Holy Spirit is central in reading the Bible, the influence of an eschatological perspective to establish interpretation practices, and the faith community as normative for interpretation reflects the unique Pentecostal ethos. To be sound as Pentecostal hermeneutics, its charismatic experiences become exemplary for interpretation practices regulated by the faith community.Contribution: The research contributes to the current Pentecostal discussion about the diversity of hermeneutical practices within the movement and the challenges and dangers some of these practices hold for the reputation and prestige of the movement.